2007
DOI: 10.1007/s10648-007-9058-z
|View full text |Cite
|
Sign up to set email alerts
|

Getting Started in Academia: A Guide for Educational Psychologists

Abstract: We identify the major tasks facing pre-tenure faculty members and outline advice, based on a review of the literature and our experiences, for succeeding in academia. The challenges encountered by new faculty include learning the culture of the new academic institution, understanding the processes and policies for academic performance review, establishing meaningful and constructive mentoring relationships, creating a sustainable research agenda as well as fostering the writing attitudes and strategies that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…Consistent with previous research, I found the task of balancing the time demands of these various roles can be difficult and has lead to the availability of time being seem as a major obstacle for academic career progression (Halpern, 2008;Mayrath, 2008) that highlights the need for effective time management. Some methods proposed to help create time and maximise efficiency include limiting classroom preparation time, setting meeting boundaries, conducting group advising sessions, trying to integrate teaching and research, removing any distractions, planning daily writing time and creating deadlines for yourself (Mayrath, 2008;McCormack & Barnes, 2008). It is also necessary to say "no" at times (Kiewra, 2008) since you can be asked to fulfil many commitments but have limited time to complete them all in and your attention can become diluted to the point where you have many goals but don"t get round to achieving them.…”
Section: Initial Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with previous research, I found the task of balancing the time demands of these various roles can be difficult and has lead to the availability of time being seem as a major obstacle for academic career progression (Halpern, 2008;Mayrath, 2008) that highlights the need for effective time management. Some methods proposed to help create time and maximise efficiency include limiting classroom preparation time, setting meeting boundaries, conducting group advising sessions, trying to integrate teaching and research, removing any distractions, planning daily writing time and creating deadlines for yourself (Mayrath, 2008;McCormack & Barnes, 2008). It is also necessary to say "no" at times (Kiewra, 2008) since you can be asked to fulfil many commitments but have limited time to complete them all in and your attention can become diluted to the point where you have many goals but don"t get round to achieving them.…”
Section: Initial Considerationsmentioning
confidence: 99%
“…However, whist waiting to get your research ideas going, there are still many things proposed to allow development as a researcher (Kiewra, 2008). These include trying to develop collaborative research links within your department, as well as external links, to allow you to work within a research team which often plays an important role in publication success (Mayrath, 2008;McCormack & Barnes, 2008). One can meet potential collaborators through meetings, courses, conferences and through actively seeking a mentor.…”
Section: A Personal Tutormentioning
confidence: 99%
See 2 more Smart Citations
“…However, the rewards of being a member of the academy may not become apparent until the academic achieves tenure. Consequently, the ability to navigate the tenure-earning process to a successful outcome is critical (Clark et al 2010;McCormick and Barnes 2008;Park et al 2011;Toews and Yazedjian 2007). The trajectory to tenure requires one to balance attention among competing demands concurrently (Bogler and Kremer-Hayon 1999;Clark et al 2010;Halpern 2008;Hershberger et al 2005), and many newly appointed assistant professors struggle with this process (Chen and Anderson 2008;Coleman et al 2006).…”
Section: Introductionmentioning
confidence: 99%